2020
DOI: 10.1021/acsami.0c04791
|View full text |Cite
|
Sign up to set email alerts
|

Acidity-Triggered Tumor-Targeted Nanosystem for Synergistic Therapy via a Cascade of ROS Generation and NO Release

Abstract: Nitric oxide (NO) gas therapy has aroused intense interest in recent years. l-Arginine (l-Arg) reacts with reactive oxygen species (ROS) in tumor cells to generate NO. This phenomenon represents an effective method for tumor therapy. However, endogenous ROS levels in most types of tumor cells cannot enable an effective reaction. β-Lapachone is generally used to increase H2O2, which can oxidize guanidine derivatives to form nitric oxide in tumor cells. In addition, based on the ferrocene (Fc)-catalyzed Fenton r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 46 publications
0
50
0
Order By: Relevance
“…Thereafter, the poly‐L‐arginine and the surface carboxyl group on the CCN were coupled to obtain ArgCCN via formation of amide bonds. The photogenerated holes with oxidizability were generated under the 660 nm laser irradiation of ArgCCN, which oxidized water to generate H 2 O 2 , and the H 2 O 2 further oxidized the arginine residues on ArgCCN to generate NO [15] . In vitro and in vivo results indicated that ArgCCN has the potential to generate NO efficiently under both normoxic and hypoxic environments, and can induce tumor cell apoptosis under laser irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, the poly‐L‐arginine and the surface carboxyl group on the CCN were coupled to obtain ArgCCN via formation of amide bonds. The photogenerated holes with oxidizability were generated under the 660 nm laser irradiation of ArgCCN, which oxidized water to generate H 2 O 2 , and the H 2 O 2 further oxidized the arginine residues on ArgCCN to generate NO [15] . In vitro and in vivo results indicated that ArgCCN has the potential to generate NO efficiently under both normoxic and hypoxic environments, and can induce tumor cell apoptosis under laser irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…As a typical radical, ● NO is the source of all RNS in the biological systems [ 125 ]. ● NO possess high reactive activity in the presence of other radicals and exhibit oxidation or nitration potential to the local biomolecules.…”
Section: Reactive Nitrogen Species-mediated Tumor Suppressionmentioning
confidence: 99%
“…[125] To enhance tumor therapeutic efficacy and decrease side effects, synergistic therapy which combines appropriate two or more modalities have been proposed to combat tumors. [126][127][128] To date, much effort has been devoted to developing smart nanoplatforms for synergistic tumor therapy, and more advances have been ; the corresponding confocal images of live and dead tumor cells which were treated with multi-hyperthermia treatments (c). C) Confocal images (upper) and SEM images (lower) of rBMSCs which were incubated with different groups of scaffolds.…”
Section: Biomaterials Scaffolds With Synergistic Tumor Therapy and Bonmentioning
confidence: 99%
“…[ 125 ] To enhance tumor therapeutic efficacy and decrease side effects, synergistic therapy which combines appropriate two or more modalities have been proposed to combat tumors. [ 126–128 ] To date, much effort has been devoted to developing smart nanoplatforms for synergistic tumor therapy, and more advances have been achieved. For example, Miao et al.…”
Section: Biomaterials Scaffolds With Synergistic Tumor Therapy and Bonmentioning
confidence: 99%